The Dynamic Mechanism on Team Effectiveness in Youth Football: A Chain Mediation - Li, Juan (Frontiers in Psychology, 2021)
This study aims to deepen our understanding of the relevant research on coach–athlete relationship theory, moral leadership, and team effectiveness theory and thus explore how to maximize team performance. As such, this study adopts an input-process-output model to explore the effect of coach–athlete relationships on team effectiveness in youth football teams. Participants in this anonymous survey included 312 young athletes, aged 13–19, from professional football schools who filled in questionnaires to provide data on the coach’s moral leadership, team effectiveness, coach–athlete relationships, and trust in the coach. The results indicate that coach–athlete relationships have a significant predictive effect on the moral leadership of coaches, which in turn, has a significant positive correlation with athletes’ trust in coaches; however, coach–athlete relationships have no direct positive correlation with team effectiveness. The coaches’ moral leadership and athletes’ trust in coaches have a chain mediation effect in the impact of coach–athlete relationships on team effectiveness. This study validates the assertion that coach–athlete relationships have a substantial effect on coach leadership. It also refines the coach–athlete relationship theory, provides evidence on the dynamic mechanism in which coach–athlete relationships affect team effectiveness, and enriches team effectiveness theory.